The compliance of Iranian library and information science journals with Thomson Reuters’ basic standards - Valizadeh-Haghi, Saeideh; Hamzehei, Ronak (Archives of Advances in Biosciences, 2018)
Presently, journals are considered as the most important tools of information science and knowledge growth throughout the world. Due to the increase in the number of scientific journals, the selection, evaluation and determination of the authenticity of these resources by the authorized organizations has attached more significance to them. Thus, the present study aims at investigating the compliance of Iranian library and information science journals with basic standards of journal evaluation through Thomson Reuters’ viewpoint. This is an applied research, which has been conducted through comparative analysis. It evaluates the authenticity of scientific journals through four basic standards of Thomson Reuters, namely on-time publishing of journals, observing international publishing laws, full-text in English, and peer review. The population of the research includes all the active scientific Iranian journals in the field of library and information sciences (12 journals). Results showed that the mean of correlation ratio between the studied journals and standards was 75%. On-time publishing and full-text in English were observed only in 33% and 58% of the studied journals respectively. However, observing international laws of publishing and peer review are in optimal status. Studies are needed in order to find out the compliance of the other countries’ library science journals with international standards, (specially developing ones) to help those countries to identify the existing gaps which will assist them to present their researches in the international level through being indexed in authentic databases. Obviously more research is needed in this area, as Thomson Reuters has published standards other than the basic standards.